Pengaruh Kepercayaan Merek Dan Kualitas Layanan Terhadap Kepuasan Pelanggan, Dampaknya Terhadap Keputusan Pemilihan Jasa Laundry Pada Anggota Tni Dan Polri Di Kota Pontianak - Delila Kumalasari; Sumin (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
TNI and Polri members often have limited time for personal activities, including washing their clothes. Therefore, efficient laundry services are needed to enable them to focus on their main tasks. The quality of washing and reliability of laundry services are crucial for TNI and Polri members. The research findings show that: 1. The coefficient value of X1 on X3 (Original Sample) is 0.369, with a P-value of 0.181 > 0.05, indicating that the result is not statistically significant, and the hypothesis on Y (Original Sample) is -0.116, with a P-value of 0.353 > 0.05, indicating that the result is not statistically significant, and the hypothesis is rejected. 4. The coefficient value of X1 on X3 on Y (Original Sample) is -0.043, with a P-value of 0.481 > 0.05, indicating that the result is not statistically significant, and the hypothesis is rejected. 5. The coefficient value of X2 on X3 on Y (Original Sample) is -0.071, with a P-value of 0.376 > 0.05, indicating that the result is not statistically significant, and the hypothesis is rejected.